2020
DOI: 10.1111/nyas.14464
|View full text |Cite
|
Sign up to set email alerts
|

Learning to run the number line: the development of attentional shifts during single‐digit arithmetic

Abstract: Solving single-digit subtraction and addition problems is associated with left and right shifts of attention in adults. Here, we explored the development of these spatial shifts in children from the third to fifth grade. In two experiments, children solved single-digit addition (Experiments 1 and 2), subtraction (Experiment 1), and multiplication (Experiment 2) problems in which operands and the arithmetic sign were shown sequentially. Although the first operand and the arithmetic sign were presented on the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…However, unlike SNAs in single numbers, SNAs in arithmetic were recently shown to be independent from the orientation of reading and writing direction as monolingual adults of opposite reading directions (i.e., Arabic and French-speaking participants) showed an identical rightward spatial bias for additions and leftward bias for subtractions (Masson et al, 2020). These different underlying roots for single numbers and arithmetic SNAs are in line with recent theoretical proposals suggesting that SNAs, despite their behavioral resemblance, could tap into distinct and independent cognitive mechanisms (Cipora et al, 2018) Mathieu et al (2016), consisting in a task in which children had to solve simple arithmetical problems with the second operand presented to the right or to the left 300 ms after the presentation of the operator (Díaz-Barriga Yáñez et al, 2020). In their first experiment, the authors showed that presenting the second operand on the left facilitated subtraction solving in 5th Graders but not in 3rd and 4th Graders.…”
Section: Introductionsupporting
confidence: 83%
“…However, unlike SNAs in single numbers, SNAs in arithmetic were recently shown to be independent from the orientation of reading and writing direction as monolingual adults of opposite reading directions (i.e., Arabic and French-speaking participants) showed an identical rightward spatial bias for additions and leftward bias for subtractions (Masson et al, 2020). These different underlying roots for single numbers and arithmetic SNAs are in line with recent theoretical proposals suggesting that SNAs, despite their behavioral resemblance, could tap into distinct and independent cognitive mechanisms (Cipora et al, 2018) Mathieu et al (2016), consisting in a task in which children had to solve simple arithmetical problems with the second operand presented to the right or to the left 300 ms after the presentation of the operator (Díaz-Barriga Yáñez et al, 2020). In their first experiment, the authors showed that presenting the second operand on the left facilitated subtraction solving in 5th Graders but not in 3rd and 4th Graders.…”
Section: Introductionsupporting
confidence: 83%
“…Contrary to what we expected, we did not find any correlation between these two variables, whatever the age of children. It is therefore possible that priming effects, and therefore automated procedures, emerge as a result of development or cognitive maturation rather than increase in arithmetic fluency per se (see also, Díaz‐Barriga Yáñez et al, 2020 for similar results and conclusions). Still, such an interpretation might seem at odds with the way Fayol and Thevenot (2012, Exp.…”
Section: Discussionmentioning
confidence: 87%
“…In turn, in the study by Díaz‐Barriga Yáñez et al. (2020), in single‐digit symbolic arithmetic, a change from a reversed directional OM in younger children (third graders) to regular OM in older children (fifth graders) was shown. In studies with adults, the plasticity of linking arithmetic operations with the direction of attention orienting depending on various factors, such as the size of the operands or, importantly, the method of focusing attention (valid cue, distractor, etc.)…”
Section: Discussionmentioning
confidence: 90%
“…Haman and Lipowska (2021), in a procedure analogous to the present study, showed a regular directional OM for non-symbolic ± 5 arithmetic and reversed OM in the ± 1 non-symbolic problem, similar to symbolic ± 1 arithmetic in the current study. In turn, in the study by Díaz-Barriga Yáñez et al (2020), in single-digit symbolic arithmetic, a change from a reversed directional OM in younger children (third graders) to regular OM in older children (fifth graders) was shown. In studies with adults, the plasticity of linking arithmetic operations with the direction of attention orienting depending on various factors, such as the size of the operands or, importantly, the method of focusing attention (valid cue, distractor, etc.)…”
Section: The Role Of Spatial Attention In Mental Arithmeticmentioning
confidence: 90%